Back Cover, Volume 1, Number 1, July 2022. Issue 1 (29th July 2022) - Xu, Jinkai; Xiu, Siyu; Lian, Zhongxu; Yu, Huadong; Cao, Jiaji
Abstract : Back Cover : The cover image is based on the Review Article Bioinspired materials for droplet manipulation: Principles, methods and applications by Xu et al.